Formulation and antibacterial effectiveness of fermented soybean husk extracts from industrial waste of tempe as eco-friendly hand sanitizer gel - Ayu Larasati; Baiq Nuraini Ayu Pita; Uswatun Hasanah Yarfaryh; Eva Haerani; Murniati Murniati (Jurnal Pijar Mipa, 2023)
This study aims to determine the formulation and antibacterial effectiveness of fermented soybean seed husk extract from tempe industrial waste as an environmentally friendly hand sanitizer gel. This type of research is an experimental study with variations in fermented soybean husk extract concentration, namely 0%, 5%, 15%, 20%, 50%, and 100%. Observational data were tested by analysis of variance ANOVA at a 5% level using Co-Stat software. Suppose there is a significant difference, a further test of Honest Significant Difference (BNJ) (organoleptic test), a further test of Orthogonal Polynomial Method (MOP) (spreadability, pH, viscosity), descriptive analysis test (flavonoid test, homogeneity test, antibacterial activity test is carried out) and test the total number of germs). The results showed that the fermented extract of soybean seed husk was positive for flavonoids, characterized by a bright yellow color change when added with 10% NaOH. The concentration of fermented soybean husk extract significantly affected the hand sanitizer gel's organoleptic properties, dispersion, total pH, and viscosity. Based on the organoleptic test, the panelists preferred the clear gel color in the F1 treatment (0%) and the thick, slightly liquid gel form with a slightly scented soybean husk in the F3 treatment (10%). The concentration treatment of soybean husk fermented extract (50%) was the best treatment based on good homogeneity, total pH 4.35, viscosity 2405 cPs, following SNI No.06-2588, and spreadability of 4.47 cm which was close to hand gel. For commercial sanitizers, the diameter of the inhibition zone against Escherichia coli bacteria ATCC 2922 and Staphylococcus aureus ATCC 2923 is 14 mm and 12 mm.